Pengaruh Penggunaan Media Visual Oleh Guru PAK Terhadap Motivasi Belajar Pendidikan Agama Kristen Siswa Kelas V SD Negeri 173210 Sigotom Kecamatan Pangaribuan Kabupaten Tapanuli Utara Tahun Pembelajaran 2022/2023 - Oktaria Ifanka Sipahutar; Betty A. S Pakpahan; Sandy Ariawan; Risden Anakampun; Simion Harianja (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
The aim of this research is to determine the positive and significant influence of the use of visual media by PAK teachers on the learning motivation of class V students at SD Negeri 173210 Sigotom, Pangaribuan District, North Tapanuli Regency for the 2022/2023 Academic Year. The method in this research is a descriptive quantitative research method. The population is all class V students of SD Negeri 173210 Sigotom, Pangaribuan District, North Tapanuli Regency, 2022/2023 Academic Year, totaling 32 people. Data was collected using a positive closed questionnaire with 31 items, namely 15 items for variable North Tapanuli Regency 2022/2023 Academic Year: 1) Test analysis requirements: a) positive relationship test obtained rxy = 0.558 > rtable(a=0.05,n=32) = 0.349. b) Testing a significant relationship obtained tcount= 3.686 > ttable(a=0.05, dk=n-2=30)= 2.042. 2) Influence test: a) Regression equation test, obtained the regression equation Y ̂=